2014
DOI: 10.1167/iovs.13-13122
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Human Retinal Microaneurysms Using Adaptive Optics Scanning Light Ophthalmoscope Fluorescein Angiography

Abstract: Retinal MAs can be classified in vivo into six different morphologic types, according to the geometry of their two-dimensional (2D) en face view. Adaptive optics scanning light ophthalmoscope fluorescein angiography imaging of MAs offers the possibility of studying microvascular change on a histologic scale, which may help our understanding of disease progression and treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 69 publications
6
123
2
1
Order By: Relevance
“…We investigated retinal microaneurysms in DME according to their location and appearance on OCTA in correlation to their clinical properties, leakage on FFA and retinal thickening on structural OCT. OCTA detected less microaneurysms than conventional FFA, but did provide information on the location of the microaneurysms in the retinal layers as well as their morphological appearances that formerly could only be appreciated using adaptive optics FFA 17. In addition, we could correlate the morphology of the microaneurysms observed on OCTA to their clinical properties, like leakage and retinal thickening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated retinal microaneurysms in DME according to their location and appearance on OCTA in correlation to their clinical properties, leakage on FFA and retinal thickening on structural OCT. OCTA detected less microaneurysms than conventional FFA, but did provide information on the location of the microaneurysms in the retinal layers as well as their morphological appearances that formerly could only be appreciated using adaptive optics FFA 17. In addition, we could correlate the morphology of the microaneurysms observed on OCTA to their clinical properties, like leakage and retinal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dubow et al , we classified the shape of the microaneurysms on OCTA into either saccular, fusiform, mixed saccular/fusiform, pedunculated, irregular or focal bulging 17. We furthermore graded the microaneurysms for the presence of focal leakage on the late phase FFA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of microaneurysms is accompanied by parietal thickening. Accordingly, an in vivo study using adaptive optics imaging8 showed that the thickness of the wall of microaneurysms increases with their diameter, and that the largest may be only partially filled with fluorescein, possibly due to the combination of parietal thickening and intraluminal material deposition.…”
mentioning
confidence: 99%
“…Rosen et al have successfully combined AOSLO and FA in order to further increase the imaging resolution and signal to noise ratio [32][33][34], which could help to address some of the image processing challenges previously discussed. In such systems, a blue channel (~488nm) light source was added for the fluorescein excitation, while maintaining the capability correcting the ophthalmic aberrations from the cornea and lens to reach theoretical limited imaging performance.…”
Section: Discussionmentioning
confidence: 99%